Understanding cost in The Meeraji Tradition: Phenomenological insights into community financial accountability in Gorontalo - Juniaty Ismail (Assets: Jurnal Akuntansi dan Pendidikan, 2025)
This study aims to explore the meaning of cost in the Meeraji tradition in Gorontalo, which contrasts with conventional economic perspectives. In capitalism, cost is typically perceived as an expenditure aimed at generating financial profit. Conversely, in the Meeraji tradition, cost is interpreted as a form of investment in spirituality, social cohesion, and cultural sustainability. This study employs a qualitative approach with interpretative phenomenological analysis. Data were collected through in-depth interviews, participatory observation, and documentation involving cultural practitioners engaged in the tradition. The findings reveal that cost in Meeraji is understood as: (1) a form of almsgiving and religious devotion, (2) a means of strengthening social bonds and mutual cooperation, and (3) a mechanism for preserving and regenerating cultural values. From an accounting perspective, these expenditures may not be classified as productive costs but, in non-profit accounting, may be recognized as program expenses under PSAK 45. The study indicates that the meaning of cost in Meeraji aligns more with the concept of the gift economy and Islamic wealth distribution than with capitalist logic. This research contributes to the literature on cultural accounting, Islamic accounting, and value-based financial reporting in tradition-oriented communities.